2016
DOI: 10.1007/s10935-016-0458-z
|View full text |Cite
|
Sign up to set email alerts
|

American Indian and Alaska Native Cancer Patients’ Perceptions of a Culturally Specific Patient Navigator Program

Abstract: Lack of access to care, funding limitations, cultural, and social barriers are challenges specific to tribal communities that have led to adverse cancer outcomes among American Indians/Alaska Natives (AI/AN). While the cancer navigator model has been shown to be effective in other underserved communities, it has not been widely implemented in Indian Country. We conducted in-depth interviews with 40 AI/AN patients at tribal clinics in Idaho and Oregon. We developed the survey instrument in partnership with comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
4
19
0
Order By: Relevance
“…Preparation for medical appointments, which sometimes included "rehearsals" with the navigator, was perceived as helpful to patients. This result is consistent with several previous studies that showed a positive relationship between navigational services and communication between the patient and the medical team (11,26,27) . Our results also con rm those of other authors that communication support is a navigational service appreciated by patients (11,26,27) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Preparation for medical appointments, which sometimes included "rehearsals" with the navigator, was perceived as helpful to patients. This result is consistent with several previous studies that showed a positive relationship between navigational services and communication between the patient and the medical team (11,26,27) . Our results also con rm those of other authors that communication support is a navigational service appreciated by patients (11,26,27) .…”
Section: Discussionsupporting
confidence: 93%
“…The navigator acts as a bridge between the health system and the biopsychosocial needs of patients, particularly those who are disadvantaged. This is consistent with previous studies that found participants' expectations of navigation service were associated with assistance around informational needs and problem solving, such as how to arrange appointments and where to go for tests (6,11) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given the unique barriers that the Alaska Native/American Indian population faces in accessing adequate health care, this study highlights a critical need for interventions tailored to the American Indian/Alaskan Natives population—whether it is education about risk factors for nasopharyngeal cancer, more frequent screening efforts to increase early detection and systemic interventions such as establishing a patient navigation systems to increase access to care and mitigate barriers to access …”
Section: Discussionmentioning
confidence: 99%
“…Navigation services can be grouped into two categories. First, pragmatic supports including, for example, assistance with referrals to support groups and counselling services [ 16 , 17 ], transportation [ 16 , 17 ], information on existing resources [ 12 , 18 , 19 ], planning appointments [ 16 , 17 , 19 , 20 ], completing forms [ 21 ], and care coordination [ 21 ]. Second, relational, interpersonal or emotional support, including, for example, assistance with decision-making [ 21 ], follow-up care [ 15 ], and response to emotional distress (e.g., listening supportively, providing comfort) [ 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%